2006
DOI: 10.6090/jarq.40.263
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the Vase Life in Cut Roses by Treatment with Glucose, Isothiazolinonic Germicide, Citric Acid and Aluminum Sulphate Solution

Abstract: Cut rose (Rosa hybrida L.) cv. Rote Rose was treated with glucose, fructose or sucrose at 10 g L -1 in combination with a commercial preparation of isothiazolinonic germicide (a mixture of 5-chloro-2-methyl-4-isothiazolin-3-one and 2-methyl-4-isothiazolin-3-one; CMI/MI; Legend MK) at 0.25, 0.5 or 1 mL L -1 . To stabilize germicidal activity, the solution was acidified by the addition of citric acid to a final concentration at 30 mg L -1 . Of the sugars, glucose was the most effective in extending the vase life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 24 publications
1
39
0
3
Order By: Relevance
“…The significant reduction in vase solution absorbance in pulsing treatments of NaOCl and HQS could be due to the antimicrobial effect of these biocides. HQS is a wellknown germicide although it is toxic to some rose cultivars leading to shortening of their vase life (Ichimura et al, 2006). Knee (2000) also reported a reduction in solution absorbance (0.057) of 'Classy' roses treated with HQC.…”
Section: Total Soluble Solids (Tss)mentioning
confidence: 99%
“…The significant reduction in vase solution absorbance in pulsing treatments of NaOCl and HQS could be due to the antimicrobial effect of these biocides. HQS is a wellknown germicide although it is toxic to some rose cultivars leading to shortening of their vase life (Ichimura et al, 2006). Knee (2000) also reported a reduction in solution absorbance (0.057) of 'Classy' roses treated with HQC.…”
Section: Total Soluble Solids (Tss)mentioning
confidence: 99%
“…Jones and Hill (1993), Kuiper et al (1995), Elhindi (2012), and Locke (2010) also reported the significance of carbohydrates and germicides for extending postharvest longevity of cut flowers. More specifically, aluminum sulfate has been reported as effective for vase life extension of several cut species, such as lisianthus (Liao et al, 2001) and roses (Ichimura et al, 2006). Addition of Kathon CG or Greenshield effectively controlled bacterial populations in the vase solutions (visual observation).…”
Section: Discussionmentioning
confidence: 99%
“…It lowers the pH of cell sap and reduces vascular blockage, thereby improving water uptake and extending longevity. Similarly, citric acid also encourages floral opening and maintains postharvest quality of cut tuberose spikes (Jowkar and Salehi, 2006), and aluminum sulfate is extensively used as a biocide for cut lisianthus (Liao et al, 2001), roses (De Stigter, 1981), and many other cut flower species and stabilizes petal anthocyanin levels to improve the keeping quality and vase life of cut roses (Ichimura et al, 2006). Several other common products have been used in homemade floral preservatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dictionary definition of an antimicrobial is "active against microorganisms" (Pearsall, 1998). Among the principle antimicrobial compounds that have been used to extend the vase life of cut flowers are: (i) chlorine and bromine compounds, such as sodium dichloroisocyanuric acid (Na-DICA) Knee, 2000;Van Doorn et al, 1990;Xie et al, 2007) and sodium hypochlorite (NaOCl) (Van Doorn et al, 1990); (ii) hydroxyquinoline (HQ) compounds, such as 8-hydroxyquinoline citrate (HQC) (Knee, 2000;Marousky, 1969;Van Doorn et al, 1990) and 8-hydroxyquinoline sulphate (HQS) (Hussein, 1994); (iii) quaternary ammonium compounds, such as benzalkonium chloride (n-alkyl dimethylbenzyl ammonium chloride) where the alkyl group may vary from C 8 H 17 to C 18 H 37 (Knee, 2000;Van Doorn et al, 1990); the proprietary compound Physan-20 (n-alkyl (C 12 and C 14 ) dimethyl ethylbenzyl ammonium chloride) (Doi and Reid, 1995); Isocil or Legend MK, where 5-chloro-2-methyl-4-isothiazolin-3-one and 2-methyl-4-isothiazolin-3-one (CMI/MI) are the active ingredients (Ichimura et al, 2006;Knee, 2000); Dantogard…”
Section: Introductionmentioning
confidence: 99%